2010
DOI: 10.1007/s12185-010-0596-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cells in essential thrombocythemia and polycythemia vera: correlation with JAK2-V617F mutational status, angiogenic factors and coagulation activation markers

Abstract: Angiogenesis plays an important role in the biology of hematological malignancies, including essential thrombocythemia (ET) and polycythemia vera (PV). Some data suggests that it has a role in the pathogenesis of thrombosis, the major clinical problem in ET and PV. The number of different subpopulations of circulating endothelial cells (CECs), plasma levels of vascular endothelial growth factor (VEGF), soluble vascular endothelial growth factor receptor 1 and 2 (sVEGFR-1,2) and placenta growth factor (PlGF) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
2
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 43 publications
5
20
2
8
Order By: Relevance
“…for PlGF [32]. Our control group shows higher levels for both biomarkers, but still significantly lower levels than PH patients.…”
Section: Discussioncontrasting
confidence: 46%
“…for PlGF [32]. Our control group shows higher levels for both biomarkers, but still significantly lower levels than PH patients.…”
Section: Discussioncontrasting
confidence: 46%
“…Our results also showed that CEC numbers are significantly higher in patients with VTE and MPN, as compared to healthy individuals. Increased numbers of CEC in patients with ET and PV have already been reported in a previous study [29].…”
Section: Discussionsupporting
confidence: 78%
“…The identification and quantification of the EC in the blood is technically very difficult and not yet well standardized [13], which probably explains the wide range of CEC numbers described in healthy individuals (4 to 7900 cells/ml) [10], [29]. Nevertheless, efforts have been made to define correctly the CEC, as well as the CEP, and there is evidence that these two EC populations can reveal endothelial injury and endothelial repair, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, the increased D-dimer level has not been proven as a clinically useful predictor for thrombosis, when compared with some other confirmed predictors such as age and history of thrombosis or leukocytosis. 26,27 In patients with ET we did not find an increase in factor VIII activity, trombinanti-thrombin complexes and prothrombin fragments F1 + F2 levels or protein C activity.…”
Section: Discussionmentioning
confidence: 51%